Insights on the potential of natural deep eutectic solvents (NADES) to fine-tune durian seed gum for use as edible food coating. (November 2022) - Fang, Xiao; Li, Yunjia; Kua, Yin Leng; Chew, Zhi Ling; Gan, Suyin; Tan, Khang Wei; Lee, Terri Zhuan Ean; Cheng, Wai Kit; Lau, Harrison Lik Nang
Abstract: Approximately 75, 000 tonnes of durian seeds are disposed to the environment every year and the amount will continue to increase due to the escalating demand for durians. The long-term accumulation of the wastes will lead to destruction of the ecological environment, and the disposal requires considerable effort. In fact, valuable products including durian seed gum and flour could be processed from the discarded durian seeds and hence, they should not be regarded as wastes. At the same time, the value of food wasted every year exceeds 1 trillion USD, of which 20% is caused by storage or shelf-life issues. After the outbreak of COVID-19, consumers tend to reduce the number of trips required to get fresh foods from the markets. Eventually, storage of larger amount of foods at extended period of time is crucial. Thus, safe and effective food preservation materials extracted from these biomasses could potentially help in reducing food wastes. Natural deep eutectic solvent (NADES) is a green solvent composed of primary metabolites (PRIM). When combined with gum into the form of eutectogel, the characteristics are tunable indicating that the properties of natural durian seed gum can be further improved for specific application. This paper discusses the potential of eutectogels formulated using NADES and durian seed gum for use as food coating. Since the coated gel is edible, potentially low in cost, and strongly sustainable, the food preservation period can be lengthened at higher commercial value. Graphical abstract: Image 1 Highlights: Eutectogel can be formulated using durian seed gum and natural deep eutectic solvents. Eutectogel produced by deep eutectic solvents is tunable based on specific requirements. Eutectogel is highly promising for use as edible gum-based food coatings. Computational tools play an important role in the formulation of NADES and eutectogel.